Validación de TILLING en evaluación de progenies endocriadas de yuca irradiada (Manihot esculenta Crantz) - Tofiño Rivera, Adriana Patricia; Cabal, D.; Ceballos, H.; Pérez, J.C.; Romero, HM (2009)
In the context set by the continuously growing agroindustrialization of cassava, and given that starch traits define tuber industrial potential, molecular tools that allow identifying variants of interest should be integrated into breeding programs for efficient selection of parental materials. The present research study compared the TILLING reverse genetics technique (modified by directly visualizing cleaved products in agarose gel) to the traditional acrylamide gel and Li-Cor platform method. Both techniques were applied to polymorphism evaluation in 10 genes with major control of the starch metabolic route. A group of 150 M2 inbred lines derived from irradiated germplasm were phenotypically identified as probable mutants and analyzed by TILLING. Only 30% of the primers used produced good quality data, for most of them amplified more than one target. Additionally, visual detection of SNPs in agarose was not achieved in mixtures of DNA templates nor in individual samples, so the results cannot be said to correspond with those obtained by Li-Cor genotyping.